Periclimenaeus colemani sp. nov. (Crustacea; Palaemonidae; Pontoniinae) from Heron island, Queensland - Bruce, A. J. (Zootaxa, 2014)
A further new species of Periclimenaeus (Crustacea: Pontoniinae) from Heron Island, Queensland, Australia, is described and illustrated. Periclimenaeus colemani sp. nov., an ascidian associate, was collected from coral reef spur and groove zone and increases to 30 the numbers of Periclimenaeus known from Australia and to 17 the number of species known from Heron Island.